2019
DOI: 10.26822/iejee.2019257665
|View full text |Cite
|
Sign up to set email alerts
|

"A Physical Education Teacher Is Like...": Examining Turkish Students Perceptions of Physical Education Teachers Through Metaphor Analysis

Abstract: The aim of this study was to determine middle school students' perceptions of physical education teachers (PETs) through metaphors and drawings. This was a qualitative study in which phenomenology and purposeful sampling were used. The study sample consisted of 200 middle school students in Ordu/Turkey in the 2017-2018 and 2018-2019 academic years. For data collection, participants were asked to fill in the blanks in the statement "The PET is like______ because ______" and to draw a picture reflecting their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
2
7
0
1
Order By: Relevance
“…Aykaç (2012) found that most secondary school students made very positive drawings to express what they thought about their teachers. Most of our participants also positively portrayed PETs in their drawings, which is consistent with the results reported by Sözen and Korur (2019). Overall, most of our participants had a favorable perception of PETs as they regarded them as caring, funny, talented, hardworking, and strong mentors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Aykaç (2012) found that most secondary school students made very positive drawings to express what they thought about their teachers. Most of our participants also positively portrayed PETs in their drawings, which is consistent with the results reported by Sözen and Korur (2019). Overall, most of our participants had a favorable perception of PETs as they regarded them as caring, funny, talented, hardworking, and strong mentors.…”
Section: Discussionsupporting
confidence: 89%
“…The second and third categories with the highest number of metaphors were "PETs as sources of information" (7.8%) and "PETs as fun people" (7.8%), respectively. Sözen and Korur (2019) also found that most secondary school students (n = 200) generated metaphors that portrayed PETs as athletic and physically strong (16%) and good people (12.5%) who guided them to the right path (9.5%). In general, research shows that students perceive teachers in a positive fashion (Kalyoncu, 2012).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, sports activities enable students to improve a comprehensive healthy lifestyle. Moreover, it particularly encourages children to participate effectively in the physical activity (Sozen & Korur, 2019). Besides that, Sports activities play a significant and prominent role in improving students' personality, through improving the self and the self-confidence concept, as well as the concept of preparedness, social responsibility, patience, and bravery (Țifrea et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While the importance of sports activities from a social point of view is less important. And the results of the (Sozen & Korur, 2019) study showed that sports activities which depend on sports skills that provide students with healthy lifestyles and healthy awareness.…”
Section: Introductionmentioning
confidence: 99%